Facilitation of Stepping with Epidural Stimulation in Spinal Rats: Role of Sensory Input - Lavrov, Igor (Society for Neuroscience, 2008)
We investigated the role of afferent information during recovery of coordinated rhythmic activity of the hindlimbs in rats with a complete spinal cord section (approximately T8) and unilateral deafferentation (T12–S2) to answer the following questions: (1) Can bilateral stepping be generated with only afferent projections intact on one side? (2) Can the sensory input from the non-deafferented side compensate for the loss of the afferent input from the deafferented side through the crossed connections within the lumbosacral spinal cord? (3) Which afferent projections to the spinal cord from the non-deafferented side predominantly mediate the effect of epidural stimulation to facilitate stepping? Recovery of stepping ability was tested under the facilitating influence of epidural stimulation at the S1 spinal segment, or epidural stimulation plus quipazine, a 5-HT agonist. All chronic spinal rats were able to generate stepping-like patterns on a moving treadmill on the non-deafferented, but not deafferented, side from 3 to 7 weeks after surgery when facilitated by epidural stimulation. Adaptation to the loss of unilateral afferent input was evident at 7 weeks after surgery, when some movements occurred on the deafferented side. Spinal-cord-evoked potentials were observed on both sides, although middle (monosynaptic) and late (long latency) responses were more prominent on the non-deafferented side. The afferent information arising from the non-deafferented side, however, eventually could mediate limited restoration of hindlimb movements on the deafferented side. These data suggest that facilitation of stepping with epidural stimulation is mediated primarily through ipsilateral afferents that project to the locomotor networks.